2022
DOI: 10.3390/jcm11082131
|View full text |Cite
|
Sign up to set email alerts
|

Premature Mortality in Type 2 Diabetes Mellitus Associated with Heart Failure and Chronic Kidney Disease: 20 Years of Real-World Data

Abstract: Introduction: Type 2 diabetes mellitus (T2D) increases the risk of heart failure (HF) and chronic kidney disease (CKD). Nonetheless, evidence of cardiovascular (CV) prognosis is relatively scarce in young T2D patients. Purpose: To estimate the risk of all-cause death, CV death, and non-fatal major CV events (MACEs) in T2D patients younger than 65 years old. Methods: We designed a retrospective cohort study using incident cases of either T2D, HF, or CKD in the population aged 40–65 years, from 1st January 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In fact, CKD is an increasingly recognized cardiovascular risk factor, associated with greater therapeutic burden, high healthcare costs and reduced life expectancy, as up to half of individuals with CKD die from cardiovascular disease [ 24–26 ]. Recently we demonstrated that the coexistence of heart failure and CKD is associated with increased premature mortality, as well as non-fatal cardiovascular events in T2DM patients <65 years old [ 27 , 28 ]. Moreover, in 2016 the European Guidelines on Cardiovascular Disease Prevention incorporated CKD as a non-traditional cardiovascular disease risk factor, readily identifiable from the analytical measurements of eGFR and UACR, and whose early identification and management may have a significant positive impact on cardiovascular disease prevention [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CKD is an increasingly recognized cardiovascular risk factor, associated with greater therapeutic burden, high healthcare costs and reduced life expectancy, as up to half of individuals with CKD die from cardiovascular disease [ 24–26 ]. Recently we demonstrated that the coexistence of heart failure and CKD is associated with increased premature mortality, as well as non-fatal cardiovascular events in T2DM patients <65 years old [ 27 , 28 ]. Moreover, in 2016 the European Guidelines on Cardiovascular Disease Prevention incorporated CKD as a non-traditional cardiovascular disease risk factor, readily identifiable from the analytical measurements of eGFR and UACR, and whose early identification and management may have a significant positive impact on cardiovascular disease prevention [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several studies concluded that inadequate physical activity raises the possibility of T2DM and CMS [ 72 - 75 ]. T2DM is the dominant cause of untimely loss of life [ 76 , 77 ]. Individuals with T2DM who are poorly therapeutically intervened often give rise to several health complications [ 78 ].…”
Section: Reviewmentioning
confidence: 99%
“… 2 , 3 Among the most important conditions in patients with CKD are the presence of heart failure (HF) and diabetes mellitus (DM) 4 , 5 ; the complex interactions between the three are referred to as the cardio‐renal‐metabolic syndrome. 6 Despite prior studies having indicated that the coexistence of any of the other conditions worsens the prognosis 7 , 8 , 9 , 10 and the increasing focus on the treatment opportunities in multidisciplinary guidelines, 11 few studies have focused on the prognosis of the overlapping cardio‐renal‐metabolic components in CKD cohorts. While new therapies such as sodium‐glucose co‐transport 2 (SGLT2) inhibitors have been developed that especially benefit patients in this intersection, studies among patients with earlier CKD stages indicate that already recommended HF treatments, such as renin‐angiotensin‐aldosterone system inhibitors (RAASis), are under‐prescribed in this population.…”
Section: Introductionmentioning
confidence: 99%